Sarcoidosis around the Globe - Mateyo, Kondwelani; Thomeer, Michiel (Seminars in Respiratory and Critical Care Medicine, 2017)
Despite sarcoidosis having a worldwide occurrence, the epidemiological map still has gaps. Prevalence and incidence rates-inconsistences have been mainly due to a lack of uniformity in study definitions as well as data collection methods. Nonetheless, studies have been consistent in showing high prevalence and incidence in Scandinavian and African American populations. Data from racially diverse populations have consistently revealed highest incidence in people of African descent. Within populations, geographical (north-to-south gradient) and time clusters have also been demonstrated from place to place. Of great interest but still elusive to researchers is the cause of sarcoidosis. The most recent focus has mostly been on Mycobacteria species and Propionibacterium acnes, but results of research thus far have been less than outright and in some cases conflicting. Environmental exposures to such substances as mold and mildew and occupations such as agricultural employment, health care work, and firefighting have been widely cited as risk factors for diseases. Certain genotypes have been linked to sarcoidosis with familial and racial clusters apparent. Some disease phenotypes have also been linked to particular genes, leaving room for further genetic research. Sarcoidosis causes multisystemic morbidity, with pulmonary, cardiac, and neurological involvement carrying the worst prognosis. Disease phenotypes vary with ethnicity, suggesting a genetic predisposition; erythema nodosum is more common in Caucasian patients, cardiac manifestations in Japanese patients, and other extrathoracic disease in black patients.
Keywords: sarcoidosis; epidemiology; incidence; prevalence; genetic predisposition; ethnicity; Mycobacteria